Perceptions 2016: An international survey of library automation - Breeding, Marshall (Anuario ThinkEPI, 2017)
Results are presented of an online survey answered by 4,042 libraries in 92 countries between November 3rd 2015 and January 18th 2017, based on their experiences with a total of 138 integrated library systems (ILS), both commercial and open source. The best products classified in the various categories analysed were Alma (Ex Libris), WorldShare Management Services (OCLC), Polaris, Apollo (Biblionix), Symphony (SirsiDynix), Opals, Library.Solution (The Library Corporation), and ByWater Solutions. The original English report was published on January 25, 2017 on the author´s website: http://librarytechnology.org/perceptions/2016
Keywords: Survey; Study; Report; Evaluation; Classification; Ranking; Software; Library systems; ILS; Automation products; Business; Public libraries; University libraries; Academic libraries; School libraries; Habits; Trends.